(untitled) (The Research of Medical Science Review, 2025)
Globally, over 296 million people are reported to use multiple types of drugs, with the prevalence of drug addiction increasing steadily. The United Nations Office on Drugs and Crime (UNODC, 2023) reported a 45% rise in drug use disorders over recent decades, affecting more than 39.5 million individuals worldwide. In Pakistan, over 7.6 million people suffer from drug addiction, with 78% being male and 22% female (UNODC, 2018). Research indicates that drug addiction in Pakistan predominantly affects individuals under the age of 30, with contributing factors including illiteracy, peer pressure, and social modeling (Masood et al., 2022). This case study explores the underlying causes and management strategies for drug addiction through the example of a 32-year-old male patient presenting with symptoms such as trembling hands, disturbed sleep, body aches, aggression, and cravings. A combination of formal and informal assessments was conducted, including structured clinical interviews, behavioral observations, the Craving Identification Chart, the Mini-Mental State Examination (MMSE), and the Drug Abuse Screening Test (DAST-20). The patient underwent 13 sessions of therapeutic interventions, including relaxation exercises, motivational interviewing, activity scheduling, and cognitive behavioral therapy (CBT). Specific CBT techniques addressed high-risk situations, coping mechanisms, goal setting, and drug refusal skills. The interventions resulted in a 50% improvement in reported symptoms. The provisional diagnosis was Alcohol Withdrawal Disorder (DSM-5 Code 291.81).